Impact Profitability, Liquidity, and Credit Risk to Market Capitalization Banking Sector on the Indonesia Stock Exchange - Sa’adah, Masrurotus; Fatihudin, Didin; Roosmawarni, Anita (PT. Global World Scientific, 2023)
This study aims to test and analyze impact profitability, liquidity, and credit risk of the banking sub-sectors on market capitalization listed on the Indonesia Stock Exchange from 2009-2018. This research method used panel data regression analysis. The sampling method of this research used a purposive sampling technique. The F-test results showed that profitability, liquidity, and credit risk simultaneously had a significant effect on market capitalization with a significance value of 0.0%. The test results with the t-test show that only profitability has a significant positive impact on market capitalization with a significance level of 0.0%. In contrast, other variables, namely liquidity and credit risk, had an insignificant effect.